Dinamika Kemitraan Antara Perum Perhutani Dengan Lembaga Masyarakat Desa Hutan (LMDH) Dalam Pelestarian Hutan Mangrove Di Pulo Cangkir Kabupaten Tangerang - Putri Anggiani; M. Dian Hikmawan (Journal of Social Politics and Governance (JSPG), 2022)
This study aims to determine the pattern of partnership that exists between Perhutani and the Forest Village Community Institution (LMDH) in the Pulo Cup mangrove forest area. Theoretically, this research is assisted by the use of partnership theory based on the principle of organizational life by Sulistyani (2004). This study uses a descriptive qualitative approach. The results of the study show that the partnership pattern is formed in a linear union of partnership because the parties involved in the partnership are institutions or organizations that have relatively similar goals and already have legality. The election of the village head of Kronjo has its own implications for the process of continuing the partnership between Perhutani and LMDH Pulo Cup and the low participation of the community results in the absence of external control from the community in the implementation of the partnership.